The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4067/s0718-381x2012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Conservative and Aesthetic Emergency Management in Adolescent with Complex Crown-Root Fracture and Simultaneous Oblique Root Fracture in Upper Maxillary Central Incisor: Clinical Outcome after 18 Months Follow-up Period

Abstract: DÍAZ, J.A.; HOPE, B. & JANS, A.Conservative and aesthetic emergency management in adolescent with complex crownroot fracture and simultaneous oblique root fracture in upper maxillary central incisor: clinical outcome after 18 months follow-up period. Int. J. Odontostomat., 6(1):27-37, 2012. SUMMARY:Emergency treatment of 11-years-old female patient, presenting a complicated crown root fracture, which simultaneously presented oblique root fracture in the maxillary right central incisor. In order to expose the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, the information of long‐term survival is rare and, mostly, includes the case‐reports, among which there are three works with a long observation period; and one stand‐alone multicenter clinical study of Andreasen et al (1995) . The latter study confirmed that the fragment reattachment was a realistic alternative to resin composite buildup for restoring esthetics and function to the traumatized dentition, and revealed the clinical factors that might predict fragment retention or loss and the frequency of pulpal complications .…”
Section: Introductionmentioning
confidence: 99%
“…However, the information of long‐term survival is rare and, mostly, includes the case‐reports, among which there are three works with a long observation period; and one stand‐alone multicenter clinical study of Andreasen et al (1995) . The latter study confirmed that the fragment reattachment was a realistic alternative to resin composite buildup for restoring esthetics and function to the traumatized dentition, and revealed the clinical factors that might predict fragment retention or loss and the frequency of pulpal complications .…”
Section: Introductionmentioning
confidence: 99%